2017
DOI: 10.1186/s40104-017-0182-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding untreated, pasteurized and acidified waste milk and bunk tank milk on the performance, serum metabolic profiles, immunity, and intestinal development in Holstein calves

Abstract: BackgroundThe present experiment was performed to assess the effects of different sources of milk on the growth performance, serum metabolism, immunity, and intestinal development of calves. Eighty-four Holstein male neonatal calves were assigned to one of the following four treatment groups: those that received bunk tank milk (BTM), untreated waste milk (UWM), pasteurized waste milk (PWM), and acidified waste milk (AWM) for 21 d.ResultsCalves in the BTM and AWM groups consumed more starter (P < 0.05) than tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 43 publications
3
34
0
5
Order By: Relevance
“…8-iso-PGA 2 = 8-iso-prostaglandin A 2 . with the resolution of inflammation (Zou et al, 2017). Brscic et al (2015) reported albumin concentrations of 36.3 g/L for healthy dry cows, which is similar to the concentrations noted in this study.…”
Section: Discussionsupporting
confidence: 86%
“…8-iso-PGA 2 = 8-iso-prostaglandin A 2 . with the resolution of inflammation (Zou et al, 2017). Brscic et al (2015) reported albumin concentrations of 36.3 g/L for healthy dry cows, which is similar to the concentrations noted in this study.…”
Section: Discussionsupporting
confidence: 86%
“…Many studies report consistent results that waste milk causes antibiotic resistance in gut bacteria (Wray et al, 1990;Aust et al, 2013;Maynou et al, 2017). As for weight gain, some reported that calves fed with waste milk had higher weight gain than those fed with milk replacer (Brunton et al, 2014) or bulk milk (Zou et al, 2017), whereas others did not observe any 2299 differences on weight gain due to milk type (Wray et al, 1990;Aust et al, 2013). The growth-promoting effect of waste milk is explained by higher nutrient density (Zou et al, 2017) or antibiotics (Aust et al, 2013) in waste milk.…”
Section: Introductionmentioning
confidence: 92%
“…As for weight gain, some reported that calves fed with waste milk had higher weight gain than those fed with milk replacer (Brunton et al, 2014) or bulk milk (Zou et al, 2017), whereas others did not observe any 2299 differences on weight gain due to milk type (Wray et al, 1990;Aust et al, 2013). The growth-promoting effect of waste milk is explained by higher nutrient density (Zou et al, 2017) or antibiotics (Aust et al, 2013) in waste milk. However, the nutrient density and antibiotics in waste milk vary in each study, which makes it difficult to determine which factor contributes to the differences in weight gain, therefore quantified antibiotics and milk replacer were used in our study to avoid the instability of waste milk.…”
Section: Introductionmentioning
confidence: 99%
“…Zou et al [20] reported that there was no difference in milk composition-milk fat, milk protein and nonfat solids-between pasteurized abnormal milk and acidified abnormal milk. In this study, the AM had no difference in lactose, milk fat, milk protein and total solids from PM, but the urea content was higher than that in PM.…”
Section: Differences In Milk Composition and Bacterial Countmentioning
confidence: 99%